On Some Issues of Legal Regulation of the Process of Execution of Budgets - Harutyunyan, Hayk (Bulletin of Yerevan University C: Jurisprudence, 2022)
The article examines the legal foundations of the budget execution, which is quite a complex process. The results of the study highlight the differences between the budget execution and the organization of the budget execution, which are not only of theoretical, but also of practical importance, since they make it possible to identify the gaps and shortcomings existing in the legal framework regulating these processes, as well as to point out the main ways to eliminate them. The article puts forward the definition of the organization of budget execution and suggests methods for improving the legal regulation thereof. In conclusion, the article suggests that the existence of the preliminary treasury control appears to be an effective way to ensure budgetary discipline, however, the legal foundations of this institution need a comprehensive and careful legal review.